Immune-Stimulatory and Therapeutic Activity of Tinospora cordifolia: Double-Edged Sword against Salmonellosis - Sultan Alsuhaibani; Masood A. Khan (Journal of Immunology Research)
The present study was aimed at determining the activity of aqueous and methanolic extracts of Tinospora cordifolia (AETC and METC) against Salmonella typhimurium. In vitro anti-Salmonella activity of T. cordifolia was determined through the broth dilution and agar well diffusion assays. The immune-stimulating potential of AETC or METC was determined by measuring the cytokine levels in the culture supernatants of treated murine J774 macrophages. Antibacterial activity of AETC or METC was determined by treating S. typhimurium-infected macrophages and BALB/C mice. The toxicity of AETC or METC was determined by measuring the levels of liver inflammation markers aspartate transaminase (AST) and alanine transaminase (ALT) and antioxidant enzymes. Macrophages treated with AETC or METC secreted greater levels of IFN-γ, TNF-α, and IL-1β. METC showed greater activity against S. typhimurium infection in macrophages and mice as well. Treatment with METC resulted in increased survival and reduced bacterial load in S. typhimurium-infected mice. Moreover, METC or AETC treatment reduced the liver inflammation and rescued the levels of antioxidant enzymes in S. typhimurium-infected mice. The results of the present study suggest that the use of T. cordifolia may act as a double-edged sword in combating salmonellosis.